IMPROVING STUDENTS’ SPEAKING SKILL THROUGH ROLE PLAY: AN ACTION RESEARCH FOR THE EIGHT GRADE STUDENTS OF SMP NEGERI 1 PEDONGGA - Mariani, Mariani; Ruslin, Ruslin; Afifah, Afifah (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2020)
Speaking is the special moment when the student can be improve their speaking in daily life or their classroom. With speaking the students can practice their knowledge of English and they can get new vocabularies. The objective of the research is to improve speaking skill for the eight grade students of SMP Negeri 1 Pedongga in the academic year of 2019/2020 with the use of role play method. Based on the observation, there were some problems in the teaching and learning of speaking. To solve those problems, the researcher implemented role play as a speaking activity.The research was carried out through action research that consisted of two cycles. Each cycle consisted of two meetings. The results of the research showed that there were some improvements in the students speaking skill. In cycle I, there were some unsuccessful actions. Meanwhile, in cycle II, the implementation of role play techniques was successful in improving the students’ speaking skill. The conclusion of this research were the students low in speaking was caused by lack in vocabulary, self-confident, and they were confused how to pronounced the word. The success in teaching doesn’t depend on the lesson program only, but more important is how to the teacher present the lesson and uses various method to manage the class.